Flexible batch electrodialysis for low-cost solar-powered brackish water desalination - He, Wei; Le Henaff, Anne Claire; Amrose, Susan; Buonassisi, Tonio; Peters, Ian Marius; Winter, Amos G. (Nature Water, 2024)
Globally, 1.6 billion people in rural regions face water scarcity. Expanding freshwater access via brackish groundwater desalination can provide additional resources to address this challenge. In this study, we have developed a time-variant electrodialysis reversal (EDR) technology that flexibly uses available solar energy for desalination. Our proposed photovoltaic-powered desalination system can vary pumping and EDR power to match the availability of intermittent solar power, maximizing the desalination rate. Our results show improved system performance with the direct use of 77% of available solar energy—91% more than in conventional systems—and a 92% reduction in battery reliance. In a village-scale desalination case study in India, these system improvements lead to a 22% reduction in water cost, making the technology competitive with the currently used on-grid, village-scale reverse osmosis systems that are mainly powered by fossil fuels. Future advances could further reduce costs, providing an improved, sustainable solution to water scarcity in remote areas.
CRIS-Team Scopus Importer:2025-04-01